ACCESS RITUAL IN EASTERN SUMBA, INDONESIA - B. Retang Wohangara (Soegijapranata Catholic University, 2013)
As a particular type of tradition, rituals have been of interest to folklorists and anthropologists. Understood as repeated, patterned, and contextualized performances, rituals could be in